Estrutura de fases da matéria de quarks quente, densa e magnetizada no modelo de Nambu–Jona-Lasinio - Duarte, Dyana Cristine (2018)
In this thesis we make use of the NJL model to the study and description of the QCD phase diagrams under different regimes of temperature, density and external magnetic fields. In our first work we study the influence of the application of an external magnetic field in the diquark condensation formation, and in the BEC-BCS crossover, in a system with two color degrees of freedom. We have dedicated special attention to the regularization of divergent integrals, and to the comparation with the smooth form factors scheme. We observe that the correct separation of the magnetic contributions is crucial to the correct description of the system, without nonphysical oscillations in the order parameters. In a second work we have studied a system with chiral imbalance, and we have shown that a method that can extract all medium contributions from divergent integrals before the regularization can explain why the well stablished chiral models such as NJL fails in the description of the behavior of the critical temperature for the chiral symmetry restoration with the increase of the chiral chemical potential m5, recently obtained by lattice QCD simulations. Furthermore we present a way to cure the problem, using a method that we call Medium Separation Scheme (MSS). Lastly, in our third work we came back to the study of BEC-BCS crossover, in a more realistic model, with three colors and including the color neutrality contidion, making use of an approximation that capture effects beyond mean field, the Optimized Perturbation Theory (OPT). We saw that the using of OPT in the case with neutrality require that the ratio between diquark and scalar coupling constants, Gd=Gs increase considerably to the BEC phase exists, and consequently the BEC-BCS crossover, when comparing with the Large Nc (or mean field) usual approximation.